Is the disappearance of the cervical flexion-relaxation phenomenon associated with cervical degeneration in healthy people? - He, Peifeng; Yang, Yunbo; Wang, Minglang; Li, Dan; Yuan, Hao; Wang, Jianxiong; He, Qiang; Feng, Daxiong; Liu, Xuanwen (European spine journal, 2024)
Purpose This study aims to explore the differences in cervical degeneration between healthy people with and without cervical flexion-relaxation phenomenon (FRP) and to identify whether the disappearance of cervical FRP is related to cervical degeneration. Methods According to the flexion relaxation ratio (FRR), healthy subjects were divided into the normal FRP group and the abnormal FRP group. Besides, MRI was used to evaluate the degeneration of the passive subsystem (vertebral body, intervertebral disc, cervical sagittal balance, etc.) and the active subsystem (deep flexors [DEs], deep extensors [DFs], and superficial extensors [SEs]). In addition, the correlation of the FRR with the cervical degeneration score, C2-7Cobb, Borden method, relative total cross-sectional area (rTCSA), relative functional cross-sectional area (rFCSA), and fatty infiltration ratio (FIR) was analyzed. Results A total of 128 healthy subjects were divided into the normal FRP group ( n =52, 40.63%) and the abnormal FRP group ( n =76, 59.38%). There were significant differences between the normal FRP group and the abnormal FRP group in the cervical degeneration score (z=-6.819, P <0.001), C2-7Cobb (t=2.994, P =0.004), Borden method (t=2.811, P =0.006), and FIR of DEs (t=-4.322, P <0.001). The FRR was significantly correlated with the cervical degeneration score ( r =-0.457, P <0.001), C2-7Cobb ( r =0.228, P =0.010), Borden method ( r =0.197, P =0.026), and FIR of DEs ( r =-0.253, P =0.004). Conclusion The disappearance of cervical FRP is related to cervical degeneration. A new hypothesis mechanism for FRP is proposed. The cervical FRP test is an effective and noninvasive examination for the differential diagnosis of healthy people, people with potential NSNP, and patients with NSNP.